Pengembangan Aplikasi UMKM Penjualan Bahan Makanan Organik Siap Antar berbasis Android - Rakha Naufal Akbar Fikri; Nurudin Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Public awareness about the importance of consuming organic foodstuffs is increasing over time. This is based on increasing public awareness of the importance of living a healthier life. Various parties also took part in pioneering the organic farming business. However, sometimes they find it difficult to trade their agricultural products. Because many people still prefer to consume food ingredients produced by conventional methods. In addition, the price of organic foodstuffs is relatively more expensive than foodstuffs produced by conventional farming methods. Thus, organic food ingredients business activists find it difficult to find buyer segmentation. To overcome the above problems, an application was built specifically to sell only organic food ingredients. This is very important to facilitate consumers of organic food ingredients so that they can get organic food ingredients correctly, quickly and easily. This application is built for the Mobile platform using the JavaScript programming language with the help of the React Native framework on the frontend, and Node.js with GraphQL middleware and MongoDB as a database on the backend. System development implements the use of the Waterfall method which emphasizes every process to be carried out systematically and gradually. Tests were carried out using white-box and black-box methods. Each technique produces valid results, which means that all functionality has been implemented properly.